The wrath of Mulgarath - DiTerlizzi, Tony.; Black, Holly (New York : Simon and Schuster Books for Young Readers, 2004)
After returning home from their latest adventure, Mallory, Jared, and Simon find Mulgarath, an ogre and leader the goblins, has taken captive their mother along with Uncle Arthur's field guide.
"Ages 7 up"--Cover, p. [4].
Keywords: Brothers and sisters -- Fiction; Goblins -- Fiction; Fairies -- Fiction; Magic -- Fiction